Species Specificity in Rodent Pheromone Receptor Repertoires - Lane, Robert P.; Young, Janet; Newman, Tera; Trask, Barbara J. (Genome Research, 2004)
The mouse V1R putative pheromone receptor gene family consists of at least 137 intact genes clustered at multiple chromosomal locations in the genome. Species-specific pheromone receptor repertoires may partly explain species-specific social behavior. We conducted a genomic analysis of an orthologous pair of mouse and rat V1R gene clusters to test for species specificity in rodent pheromone systems. Mouse and rat have lineage-specific V1R repertoires in each of three major subfamilies at these loci as a result of postspeciation duplications, gene loss, and gene conversions. The onset of this diversification roughly coincides with a wave of Line1 (L1) retrotranspositions into the two loci. We propose that L1 activity has facilitated postspeciation V1R duplications and gene conversions. In addition, we find extensive homology among putative V1R promoter regions in both species. We propose a regulatory model in which promoter homogenization could ensure that V1R genes are equally competitive for a limiting transcriptional structure to account for mutually exclusive V1R expression in vomeronasal neurons.
10.1101/gr.2117004